A Novel Model of Lethal Hendra Virus Infection in African Green Monkeys and the Effectiveness of Ribavirin Treatment - Rockx, Barry (American Society for Microbiology (ASM), 2010)
The henipaviruses, Hendra virus (HeV) and Nipah virus (NiV), are emerging zoonotic paramyxoviruses that can cause severe and often lethal neurologic and/or respiratory disease in a wide variety of mammalian hosts, including humans. There are presently no licensed vaccines or treatment options approved for human or veterinarian use. Guinea pigs, hamsters, cats, and ferrets, have been evaluated as animal models of human HeV infection, but studies in nonhuman primates (NHP) have not been reported, and the development and approval of any vaccine or antiviral for human use will likely require efficacy studies in an NHP model. Here, we examined the pathogenesis of HeV in the African green monkey (AGM) following intratracheal inoculation. Exposure of AGMs to HeV produced a uniformly lethal infection, and the observed clinical signs and pathology were highly consistent with HeV-mediated disease seen in humans. Ribavirin has been used to treat patients infected with either HeV or NiV; however, its utility in improving outcome remains, at best, uncertain. We examined the antiviral effect of ribavirin in a cohort of nine AGMs before or after exposure to HeV. Ribavirin treatment delayed disease onset by 1 to 2 days, with no significant benefit for disease progression and outcome. Together our findings introduce a new disease model of acute HeV infection suitable for testing antiviral strategies and also demonstrate that, while ribavirin may have some antiviral activity against the henipaviruses, its use as an effective standalone therapy for HeV infection is questionable.